PENGARUH PROFITABILITAS, LIKUIDITAS, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PERINGKAT OBLIGASI - Miky Ardianus K. Tokan; Maria Yovita R. Pandin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of profitability, liquidity, company growth, company size, and leverage on the bond ratings of companies listed on the IDX for the period 2018 – 2022. The samples used in this study were 9 companies. The sampling method uses purposive sampling method. Sources of data are secondary data in the form of annual financial reports of companies listed on the IDX and Indonesian stock rankings. The data analysis technique in this study used the SPSS version 29.0 application with several kinds of tests, namely the classic assumption test, among others, Multicollinearity Test, Heteroscedasticity Test, Normality Test and partial hypothesis test (t test) and simultaneous test (f test). The results showed that profitability has an effect on bond ratings, liquidity has no effect on bond ratings, company growth has no effect on bond ratings, company size has no effect on bond ratings, and leverage has an effect on bond ratings